Novel cyclostationary multiple antenna spectrum sensing approach based on asymptotic optimal χ2 test - Qing-lei KONG; Yu-long GAO (Tongxin xuebao)
In order to improve the performance of cyclostationary spectrum sensing,reduce the influence of deep fading,a new approach of combining the multiple received signals by multiple antennas was proposed,which means that exploited an improved MRC combination of cyclic autocorrelation and cyclic spectrum,and got the test statistic calculated by implementing asymptotic optimal χ2 test.This approach could detect the existence of the transmitting signal without amplitude prior information.BPSK modulation signal was applied as an example to testify the accuracy of the approach.The results indicate that multiple antennas spectrum sensing has more advantage that single antenna,reduces the influence of deep fading.